Analysis of the Driving Factors of Property Investment in the Peri-Urban Property Market of Ogun State, Nigeria - Ajayi, Cyril Ayodele (Department of Estate Management, Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
This study examined the driving factors of property investment in the periurban property market with a major focus on Abeokuta suburbs. It was done with a view to providing information on the types of real estate property developed for investment purposes and the prominent market driving forces in the suburb. The study used primary data and the relevant information was collected through a structured questionnaire instrument. The study employed convenience sampling techniques. A total of 150 questionnaires were administered to members of Nigeria Institution of Estate Surveyors and Valuers (NIESV) and Real Estate Developers Association of Nigeria (REDAN). Eighty-two (82) and seventy-forty (74) questionnaire were retrieved from NIESV and the REDAN respectively. The study deployed descriptive statistics such as simple frequency distribution and meanstandard deviation model to analyse the data. The study found that in the suburb, the property types such as residential and commercial were identified to be the most often developed investment property types and major businesses occur in buying and selling of investment property among the trading activities in the market. The prominent driving forces were land availability and affordability, economic gain/market potential, proximity to urban centres, population growth and strategic locational features. This result signals the need for potential real estate investors to consider the driving forces as underlying factors for informed decision when thinking of investing in the peri-urban property market.
Keywords: Drivers; Peri-urban; Property-market; Urbanisation